Analysis of Acute Poisoning Cases Presenting to the Medical Emergency Department - Qudsia Nuzhat; Simhadri V. S. D. N. A. Nagesh; Parthajyoti Neog; Sujata Singh; Kaustav Kumar Bairagi (Journal of Forensic Science and Medicine)
Introduction: Acute poisoning cases are always a medical emergency. Immediate management with proper identification of the poisoning agent is very much important. This study aimed to estimate the sociodemographic pattern and outcome of acute poisoning cases so that the emergency health-care provider can decide on a suitable management procedure as well as effective preventive measures as early as possible when they receive a patient. Materials and Methods: A retrospective observational study was carried out for a 1-year duration after getting approval from the Institutional Ethical Committee. Patients of either gender with acute poisoning were collected from the records of the medical emergency department of the hospital with the details of age, gender, occupation, type of poisoning, route of administration, and outcome. Analysis was done with suitable software. Results: We got a total of 91 acute poisoning cases, where 61 (67.03%) patients survived and 30 (32.96%) patients succumbed to death. The highest cases were seen due to aluminum phosphide (ALP) and it was about 47 (51.64%), followed by organophosphorus (OP) 21 (23.07%). The most common age group was early adulthood (20–30 years) followed by the adolescence (10–19 years) age group. Male cases were 50 (54.94%) compared to females 41 (45.05%) and married cases were 51 (56.04%) compared to unmarried cases 40 (43.95%). Conclusions: ALP poisoning was highest followed by OP, and all cases were suicidal in intention. Male cases were higher than female cases. Delayed reporting to the hospital significantly increased the death rate.